Drought Conditions Maximize the Impact of High‐Frequency Flow Variations on Thermal Regimes and Biogeochemical Function in the Hyporheic Zone. Issue 10 (4th October 2018) - Song, Xuehang; Chen, Xingyuan; Stegen, James; Hammond, Glenn; Song, Hyun‐Seob; Dai, Heng; Graham, Emily; Zachara, John M.
Abstract: Anthropogenic activities, especially dam operations, often induce larger and more frequent stage fluctuations than those occurring in natural rivers. However, long‐term impacts of such flow variations on thermal and biogeochemical dynamics of the associated hyporheic zone (HZ) are poorly understood. In this study, we built a heterogeneous, two‐dimensional, thermo‐hydro‐biogeochemical model for an aerobic respiration dominated river system. Our results revealed important interactions between subdaily to weekly flow variations and mean flow conditions controlled by snowpack at the watershed. High‐frequency stage fluctuations had their strongest thermal and biogeochemical impacts when mean river stage was low during fall and winter. In an abnormal drought year (2015) with low river stages during summer and early fall, high‐frequency stage fluctuations caused the HZ to be warmer than average. Furthermore, high‐frequency stage fluctuation enhanced all biogeochemical reactions by increasing nutrient supply and creating more oxygenated conditions. Overall carbon consumption in the HZ increased due to high‐frequency flow variations. Thermal dynamics altered by high‐frequency stage fluctuation impacted biogeochemical reactions in the HZ less than effects imposed by enhanced nutrient and oxygen supply. In addition to these results, we demonstrated that the HZ's hydrogeologic properties control flow paths that influence residence times and nutrient supply and consequently control spatial distribution of biogeochemical reaction hot spots in the HZ. Here we provide scientific basis for assessing potential ecological consequences of high‐frequency flow variations in a regulated river, as well as guidance for maximizing potential benefits—or minimizing drawbacks—of dam regulation to riverine ecosystems. Key Points: High‐frequency flow variations enhance hydrologic exchange and create long‐term alterations to thermal regimes and biogeochemical reactions High‐frequency flow variations have the largest impact on thermal regimes and biogeochemical reactions in hyporheic zone under drought Spatial distribution of biogeochemical hot spots depends more on the subsurface hydraulic properties than high‐frequency flow variations